The spatial distribution of planetary ion fluxes near Mars observed by MAVEN. Issue 21 (5th November 2015) - Brain, D. A.; McFadden, J. P.; Halekas, J. S.; Connerney, J. E. P.; Bougher, S. W.; Curry, S.; Dong, C. F.; Dong, Y.; Eparvier, F.; Fang, X.; Fortier, K.; Hara, T.; et al.
Abstract: We present the results of an initial effort to statistically map the fluxes of planetary ions on a closed surface around Mars. Choosing a spherical shell 1000 km above the planet, we map both outgoing and incoming ion fluxes (with energies >25 eV) over a 4 month period. The results show net escape of planetary ions behind Mars and strong fluxes of escaping ions from the northern hemisphere with respect to the solar wind convection electric field. Planetary ions also travel toward the planet, and return fluxes are particularly strong in the southern electric field hemisphere. We obtain a lower bound estimate for planetary ion escape of 3 × 10 24 s −1, accounting for the 10% of ions that return toward the planet and assuming that the 70% of the surface covered so far is representative of the regions not yet visited by Mars Atmosphere and Volatile EvolutioN (MAVEN). Key Points: MAVEN ion measurements are mapped to a spherical surface around Mars Planetary ion fluxes are organized in four spatial regions on the shell Heavy ion escape rates exceed 2 × 10 24 s −1 for energies >25 eV